Entwicklung und Anwendung eines photochemischen schräge Säulen Modell-Paketes zur Interpretation von DOAS-Daten atmosphärischer Spurengase - Mueller, Richard (Univ. Bremen, 2001)
Besides measurements of atmospheric trace gases and laboratory studies of chemical reactions, modelling has been recognised to be of increasing importance to improve our knowledge of the atmosphere and the capabilities of photochemical models. Main scope of this work was the development of a photochemical atmospheric model, which was especielly designed for the interpretation of Differential Optical Absorption measurments (DOAS). This model has been used to improve our knowledge of atmospheric chemistry. For example, for the first time it was possible to demonstrate that a significant amount of IO in a range of 0.65 to 0.8 pptv is present in the stratosphere in the polar region (Ny-Alesund,Spitzbergen). Moreover it has been shown that such amounts of stratospheric IO lead to an additional Ozone loss in the range of 10 % in cold arctic winters. : thesis